2018
DOI: 10.1016/j.anifeedsci.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of corn silage with Lactobacillus plantarum and Bacillus subtilis associated with amylolytic enzyme supply at feeding. 2. Growth performance and carcass and meat traits of lambs

Abstract: The objective of this research was to investigate the effects of inoculation of corn silage and dietary supplementation of amylolytic enzymes, and their interaction, on lamb growth performance and carcass and meat traits. Whole-crop corn forage was treated either with water (untreated) or with Lactobacillus plantarum MA 18/5U at 1 × 10 5 cfu/g fresh forage combined with Bacillus subtilis AT553098 at 1 × 10 5 cfu/g fresh forage (inoculated) and ensiled for 170 d. Forty non-castrated Texel × Dorper male lambs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
1
6
0
1
Order By: Relevance
“…Despite of amylolytic enzymes have potential to increase nutrients digestibility by acting on starch-protein matrix, which could 230 enhance microbial attachment and enzymatic digestion of starch granules (Giuberti et al, 2014), no beneficial responses were observed 231 on nutrient intake and digestibility. The same was observed by Lara et al (2018), evaluating lambs fed corn silage with inoculant alone 232 or in combination with amylolytic enzymes. 233 Enzyme aditives are mostly applied in combination with bacterial inoculants (Muck et al, 2018), as observed in this study, where 234 we added to all treatments microbial aditive composed by Lactobacillus plantarum and Pediococcus acidilactici.…”
Section: Ensiling 217supporting
confidence: 67%
“…Despite of amylolytic enzymes have potential to increase nutrients digestibility by acting on starch-protein matrix, which could 230 enhance microbial attachment and enzymatic digestion of starch granules (Giuberti et al, 2014), no beneficial responses were observed 231 on nutrient intake and digestibility. The same was observed by Lara et al (2018), evaluating lambs fed corn silage with inoculant alone 232 or in combination with amylolytic enzymes. 233 Enzyme aditives are mostly applied in combination with bacterial inoculants (Muck et al, 2018), as observed in this study, where 234 we added to all treatments microbial aditive composed by Lactobacillus plantarum and Pediococcus acidilactici.…”
Section: Ensiling 217supporting
confidence: 67%
“…DMI tended to be greater ( P < 0.08) for calves fed EFC-S over the entire 91-d trial, and this tendency became apparent as early as day 42 of the trial. Lara et al (2018b) researched effects of feeding corn silage diets with or without an amylolytic enzyme supplemented to lambs. They found that providing 602 dextrinizing units of alpha-amylase/kg DM in the total mixed ration had no effect on DMI or ADG, and, although not significant, G:F was improved by 4.8% for lambs fed corn silage with an alpha-amylase supplement.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of NH 3 -N is dependent on dietary crude protein levels and the rate of microbial breakdown and metabolism. Higher concentrations of NH 3 -N generally favor microbial protein synthesis ( Basso et al, 2018 ; Lara et al, 2018 ). In this study, no significant differences in rumen fluid NH 3 -N concentrations were observed among the groups.…”
Section: Discussionmentioning
confidence: 99%